Realization of Security Concepts for DICOM-based Distributed Medical Services - Bernarding, J.; Thiel, A.; Tolxdorff, T. (Methods of Information in Medicine, 2000)
Exploiting distributed hard- and software resources for tele-medicine requires a fast, secure, and platform-independent data exchange. Standards without inherent security mechanisms such as DICOM may ease non-authorized data access. Therefore, exemplary telemedical data streams were analyzed within the Berlin metropolitan area network using specialized magnetic resonance imaging techniques and distributed resources for data postprocessing. For secure DICOM communication both the Secure Socket Layer Protocol and a DICOM-conform partial encryption of patient-relevant data were implemented. Partial encryption exhibited the highest transfer rate and enabled a secure long-term storage. Different data streams between secured and unsecured networks were realized using partial encryption.
Keywords: Telemedicine; Secured Data Transfer; DICOM; PACS; ATM